A Tale of Two Four-horned Antelopes Ram and Sita - Jagannatha Shetty, B. (Indian Forester, 1973)
On 24th March 1973 Sita the four-horned antelope gave birth to 2 male fawns in captivity. On the fifth day one of the twins died. Behaviour of Sita, when separated with her fawns from her mate, Ram, indicated her yearning fur his companionship. This happening has also helped us to have a check on certain of the recorded data relating to the species and generally to add to our knowledge of the subject.